Implementation Plan in Response to Board-Endorsed Recommendations for the IEO Evaluation of International Reserves : IMF Concerns and Country Perspectives. (Policy Papers; Policy Paper ;, 2013)
This paper proposes Management's response to the IEO's Evaluation of International Reserves-IMF Concerns and Country Perspectives. The proposed implementation plan focuses on those recommendations that are not already being addressed by other recent Fund initiatives, and include: (i) a successor paper on reserve adequacy, which will review the work contained in the Fund's 2011 Assessing Reserve Adequacy paper and develop additional and updated guidance where needed; (ii) the preparation of a staff guidance note for assessing adequacy; and (iii) additional engagement on reserve issues with members, the private sector, and academics.